Reconfiguring HR Roles for Sustainability Governance: A Bibliometric View of Strategic Role Transformation - Judijanto, Loso; Rosid, Muhammad Abdul; Mayratih, Siska; Isrok, Isrok (West Science Social and Humanities Studies, 2025)
As organizations increasingly face pressure to align with sustainability goals and adapt to rapid digital transformation, the role of Human Resource Management (HRM) is undergoing a strategic redefinition. This study investigates the evolution of HR’s contribution to sustainability governance through a comprehensive bibliometric analysis of scholarly literature indexed in the Scopus database from 2000 to 2025. Using VOSviewer for co-occurrence, temporal, and density mapping, the research identifies major thematic clusters including green HRM, digital transformation, employee engagement, and artificial intelligence. The study also maps institutional and international collaborations, revealing India as a central hub in sustainability-oriented HR research. Findings highlight the growing scholarly focus on integrating technology and sustainability into HR functions, positioning HR as a critical enabler of ethical decision-making and organizational transformation. This research offers theoretical contributions by structuring fragmented themes into coherent domains and provides practical implications for HR professionals, educators, and policymakers. Limitations include reliance on a single database and the exclusion of qualitative content analysis, suggesting directions for future mixed-method research.